Photoadaptation of two members of the Chlorophyta (Scenedesmus and Chlorella) in laboratory and outdoor cultures: changes in chlorophyll fluorescence quenching and the xanthophyll cycle - Masojídek, J; Torzillo, G; Koblízek, M; Kopecký, J; Bernardini, P; Sacchi, A; Komenda, J (Planta, 1999)
The role of the xanthophyll cycle in the adaptation of two chlorococcal algae Scenedesmus quadricauda and Chlorella sorokiniana to high irradiance was studied under laboratory and outdoor conditions. We wished to elucidate whether the xanthophyll cycle plays a key role in dissipating the excesses of absorbed light, as in higher plants, and to characterise the relationship between chlorophyll fluorescence parameters and the content of xanthophyll-cycle pigments. The xanthophyll cycle was found to be operative in both species; however, its contribution to overall non-photochemical quenching (NPQ) could only be distinguished in Scenedesmus (15-20% of total NPQ). The Scenedesmus cultures showed a larger pool of xanthophyll-cycle pigments than Chlorella, and lower sensitivity to photoinhibition as judged from the reduction of maximum quantum yield of photosystem II. In general, both algae had a larger xanthophyll-cycle pool when grown outdoors than in laboratory cultures. Comparing the two species, Scenedesmus exhibited a higher capacity to adapt to high irradiance, due to an effective quenching mechanism and high photosynthetic capacity; in contrast, Chlorella represents a species with a larger antennae system, less-efficient quenching and lower photosynthetic performance. Non-photochemical quenching (NPQ) induced through the xanthophyll cycle can, to a limited extent, represent a regulatory factor in diluted algal cultures grown in outdoor solar photobioreactors, as well as in natural algal phytoplankton populations exposed transiently to high irradiance. However, it does not play an appreciable role in dense, well-mixed microalgal suspensions.
Keywords: fluorescence; chlorofyl; Chlorella; Fluorescence; Photosynthesis; Chlorophyta; Chlorophyll; fyziologická adaptace; lutein; Lutein; fotosyntéza; Adaptation, Physiological